2018
DOI: 10.2196/mhealth.9754
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Validity of Current Mainstream Wearable Devices in Fitness Tracking Under Various Physical Activities: Comparative Study

Abstract: BackgroundWearable devices have attracted much attention from the market in recent years for their fitness monitoring and other health-related metrics; however, the accuracy of fitness tracking results still plays a major role in health promotion.ObjectiveThe aim of this study was to evaluate the accuracy of a host of latest wearable devices in measuring fitness-related indicators under various seminatural activities.MethodsA total of 44 healthy subjects were recruited, and each subject was asked to simultaneo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
146
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 258 publications
(179 citation statements)
references
References 28 publications
6
146
0
4
Order By: Relevance
“…However, consumer acceptance of wearable devices has not been as positive as expected. Many important issues that affect the ultimate adoption of wearable devices by consumers have been investigated, including the reliability [ 23 , 24 ] and validity of the measures that they monitor [ 25 - 27 ]. In addition, studies have confirmed that the key to a product’s success is the acceptance of wearable products by ordinary consumers and the comfort level of these products; product usability is an important aspect of this [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, consumer acceptance of wearable devices has not been as positive as expected. Many important issues that affect the ultimate adoption of wearable devices by consumers have been investigated, including the reliability [ 23 , 24 ] and validity of the measures that they monitor [ 25 - 27 ]. In addition, studies have confirmed that the key to a product’s success is the acceptance of wearable products by ordinary consumers and the comfort level of these products; product usability is an important aspect of this [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that most wearable devices do not produce a valid quantification of energy expenditure. Xie et al [26] compared six devices and two smartphone apps regarding their ability to measure major health indicators (e.g., heart rate or number of steps) under various activity states (e.g., resting, running, and sleeping). They found that the devices had high measurement accuracy for all health indicators except energy consumption, but there was variation between devices, with certain ones performing better than others for specific indicators in different activity states.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Manufacturers of CWDHs often make strong claims about the accuracy and reliability of their devices [13]. However, there are genuine concerns over the accuracy of the data collected by CWHDs [14]. For example accelerometer and pedometer-based CWHDs are known to be inaccurate in their estimation of energy expended (EE), and are unable to accurately track the number of steps in PA like cycling [6,7].…”
Section: Introductionmentioning
confidence: 99%